(untitled) (Journal of the College of Basic Education, 2022)
Mythology is considered one of the universal cultural colors that people have expressed through the arts of literature and epics. He is considered the first person to discover fictional and nonfiction literature and its development. His book was known Epic literature, poetry, chanting, singing, wisdom literature and other arts, of which we are interested here. The Epic (Gilgamesh), which included in its aspects most of these artistic and literary colors, as well as evidence implicit arts that refer to the arts of architecture, construction, sculpture, goldsmithing, casting, artistic crafts, and others, which